2017
DOI: 10.1117/1.jbo.22.4.047001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intraocular pressure sensing using an implanted reflective flexible membrane

Abstract: Glaucoma is a neurodegenerative condition that is the leading cause of irreversible blindness worldwide. Elevated intraocular pressure (IOP) is the main cause for the development of the disease. The symptoms of this form, such as deterioration of vision and scotomas (loss of visual fields), appear in the latter stages of the disease. Therefore, an IOP monitoring device is needed for better, simpler, and faster diagnosis, and to enable a fast treatment response. We present a theoretical assessment as well as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous studies related to smart contact lenses employed various methods, e.g., fabrication of a pattern on a transparent film and its incorporation onto a soft lens, pattern transfer after photolithography, laser interference patterning, , and near-field subdiffraction photolithography . The smart lenses resulting from these processes are used for glucose-level measurement, ,, intraocular pressure measurement, , dry eye prevention, , and color blindness correction. , The process developed in this study was employed to transfer an HA film, nanopatterned with an Al nanoline array, onto a hydrogel-based soft contact lens made of narafilcon A with a water content of 46 wt %. , …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies related to smart contact lenses employed various methods, e.g., fabrication of a pattern on a transparent film and its incorporation onto a soft lens, pattern transfer after photolithography, laser interference patterning, , and near-field subdiffraction photolithography . The smart lenses resulting from these processes are used for glucose-level measurement, ,, intraocular pressure measurement, , dry eye prevention, , and color blindness correction. , The process developed in this study was employed to transfer an HA film, nanopatterned with an Al nanoline array, onto a hydrogel-based soft contact lens made of narafilcon A with a water content of 46 wt %. , …”
Section: Resultsmentioning
confidence: 99%
“…The IOP sensor introduced extra aberration due to its flexible surface geometry. 43 The native aberration of the sensors (0.168 AE 0.014 μm) accounts for the increase in the average aberration in Fig. 3(b) (0.514 μm) when compared with that in Fig.…”
Section: Influence Of Optical Aberrations On Snr Of Optical Readoutmentioning
confidence: 90%
“…This trend is consistent with the previous study that showed that the second-order rms-wavefront error originating from a deflected membrane was more sensitive to IOP than the fourth-and higher-order rms-wavefront errors. 43 When the sensors were implanted at three different radial distances from the pupil center in the anterior chamber [Figs. 4(a) and 4(b)], however, the first-order Zernike coefficients became the dominant factor that increased the total rms-wavefront error [ Fig.…”
Section: Influence Of Optical Aberrations On Accuracy Of Optical Iop mentioning
confidence: 99%
See 1 more Smart Citation
“…However, accurate IOP measurements are highly dependent on patient cooperation and corneal characteristics, such as central corneal thickness (CCT), corneal curvature, hydration, elasticity, hysteresis, and rigidity [5,[9][10][11][12], requiring real-time systems to know the biomechanical properties of the cornea to then compensate in the IOP measurement, such as with the ocular response analyzer (ORA; Reichert Ophthalmic Instruments, Depew).…”
Section: Introductionmentioning
confidence: 99%